PENGUATAN KEMANDIRIAN PETANI MENUJU PERTANIAN BERKELANJUTAN MELALUI PEMBUATAN PUPUK ORGANIK DI DESA SEPUTIH, JEMBER - Widodo, Tirto Wahyu; Alif, Trisnani; Soelaksini, Liliek Dwi; Arisandi, Dewi Puspa; Galushasti, Andarula; Irawan, Triono Bambang; Putri, April Lian; Hidayat, Heppy Yuniar Ariani (Department of Agronomy, Faculty of Agriculture, University of Jember, 2025)
The majority of the population in Seputih Village, Mayang District, Jember Regency, operates in the agricultural sector. A common problem in farming is the scarcity of synthetic chemical fertilizers for farmers. Therefore, this activity aims to provide information on the independent production of alternative fertilizers by farmers, namely organic fertilizers. The implementation method includes initial observation, outreach, monitoring, and evaluation. The results of this activity have had a positive impact on farmers' knowledge of independent organic fertilizer production. Farmer knowledge increased from 63% to 82.2%. The results of this activity are expected to encourage farmers' independence in solving agricultural problems and supporting environmentally friendly agricultural sustainability.